The Rise of Technosocialism How Inequality, AI and Climate Will Usher in a New World. - King, Brett (Marshall Cavendish International (Asia) Private Limited, 2021)
What is the impact of COVID-19 on world economies? If the cost of providing universal health care is lower than the cost of building a political movement to prevent it, would politicians still view it as socialism? In a world where algorithms and robots take the jobs of immigrants and citizens alike, are border controls an effective response? If unemployment skyrockets due to automation, would conservative governments rather battle long-term social unrest, or could they agree on something like universal basic income? When renewable energy sources are a fraction of the cost of coal generated el.